CHANGES IN THE CHEMICAL COMPOSITION OF DRINKING GROUNDWATER OF THE KHERSON DEPOSIT ACCORDING TO LONG-TERM OBSERVATIONS IN PRE-WAR TIMES - KOSHLIAKOVA, Tetiana; KOSHLIAKOV, Оleсsiі (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. After the destruction of the Kakhovskaya HPP and the spillway dam, and devastation of the Kakhovskaya Reservoir, the issue of water supply to the south of Ukraine became very acute. This problem is the most painful for the Kherson region. In this regard, there was a need to conduct monitoring studies on the quality of groundwater, which serves as a source of water supply for the population of Kherson. The analysis of changes in the main indicators of the chemical composition of groundwater over time makes it possible to assess potential risks for the health of consumers and to obtain predictive assessments of the state of the studied hydrogeological system.Methods. When performing the work, mathematical-statistical, graph-analytical research methods were applied, comparative analysis was performed, and constructions were carried out using the specialized software tool GW_Chart.Results. A high correlation was found between the amount of water withdrawal and permanganate oxidizability and fluorine content. It was established that during the studied period of time (from 2009 to 2021) there were changes in the general chemical composition of groundwater – in the cationic composition there was a transition from a calcium-magnesium to a sodium-potassium, in the anionic composition – from chloride- hydrocarbonate to bicarbonate-chloride. A non-carcinogenic risk assessment was performed using the non-threshold method for Mn and F. It was found that the danger level for F is extremely high, and for Mn – catastrophic.Сonclusions. The authors made the conclusion that groundwaters in the Upper Sarmatian sediments, which are exploited by the majority of examined wells on the territory of Kherson, have a complex direction of changes in chemical composition, depending on the conditions of their formation, which are determined by a complex of natural and man-made factors. The key role is played by: filtration properties of confining bed layers in the roof of the aquifer; consequences of the discharge of domestic sewage to Meotis-Pont deposits; lack of centralized sewerage within the private sector; recharge with surface waters of the Dnipro River; design features of the wells; operating loads on the aquifer. In general, it can be stated that the qualitative composition of groundwater has undergone significant changes. All these factors give the territory of the deposit a clearly defined lateral and in some cases, vertical hydrochemical zonation of groundwater.
Keywords: groundwater; hydrogeochemistry; Kherson deposit; monitoring studies; risk assessment